How government incentives shape consumer intention to adopt electric vehicles: A study in Batam City - Saputra, Suyono; Yulfiswandi, Yulfiswandi; Yuwono, Wisnu (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2024)
This study analyzes the factors influencing the intention to purchase electric vehicles (EVs) following the implementation of financial incentives. It integrates the Theory of Planned Behavior (TPB), the Technological Acceptance Model (TAM), and extensions of TPB, including consumer knowledge, perceived risk, and financial incentives. Data were collected from 384 respondents, comprising both EV users and non-users in Batam City. The findings reveal that attitude has an insignificant effect on the intention to buy EVs, while perceived usefulness also shows an insignificant effect on attitude. In contrast, consumer knowledge and financial incentives significantly influence both attitude and purchase intention. Perceived risk negatively affects attitude and intention to buy EVs. The study highlights the need for policies providing financial incentives to consider long-term benefits for consumers to ensure sustainable adoption of EVs.